Maximal constant 45 min running velocity gives maximal lactate steady state - Vobejda, C.; Wortmann, T.; Zimmermann, E. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the present study was to improve and confirm a time trial (TT) based method for determining anaerobic threshold (AnT) requiring minimal equipment. Methods: Eighteen participants underwent three to five all-out TTs for at the most 60 min. Velocity of the TTs was adapted in 0.1 or 0.2 m/s steps until maximal velocity maintainable for at least 45 min (Vmax45) was identified. Exercise was interrupted every 5 min in order to take blood samples. After the participants had finished their last TT blood lactate concentration (BLC) was determined to identify maximal lactate steady state (MLSS). Results: Velocity, BLC and heart rate (HR) at the TTs giving MLSS (TTMLSS) and giving Vmax45 (TTVmax45) were almost identical (3.45±0.31 m/s vs. 3.44±0.31 m/s, 4.46±1.28 mmol/L vs. 4.52±1.28 mmol/L, 177±9.8 bpm vs. 178±9.4 bpm). Coefficient of correlation (R) and standard error of estimate (SEE) between velocity at MLSS (VMLSS) and Vmax45 were 0.96 and 0.09 m/s, respectively, indicating a very close relationship. Agreement between VMLSS and Vmax45 was also very high. At VMLSS cardiovascular drift (CVD) was 8.4±2.6 bpm from the 10th to 30th min. At Vmax45 CVD was 7.9±2.8 bpm from the 10th to 30th min and 11.2±3.8 bpm from the 10th to 45th min. Conclusion: Determination of Vmax45 is a manageable, cost-saving and precise method for predicting velocity and CVD at MLSS in healthy, ambitious and at least moderately trained runners.